2021
DOI: 10.21744/ijhms.v4n2.1747
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Averrhoa bilimbi leaf extract on spermatogenic cells of mice (Mus Musculus L.) hyperglycemia

Abstract: The purpose of this study was to determine the effect of giving Averrhoa bilimbi leaf extract on sperm quality of diabetic mice. This research is a pure experimental (true experimental) with a post-test-only control group design approach. This research was conducted by giving Averrhoa bilimbi leaf extract as a treatment for 42 days in male mice. Sperm quality parameters observed included viability, abnormalities, motility in sperm. In all variables, the results of the data showing a normal distribution with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
(22 reference statements)
2
8
0
Order By: Relevance
“…Firstly: The results of the current study showed a clear increase in the concentration of liver enzymes in the blood serum of animals treated with sodium benzoate at a concentration of (250) mg / kg of body weight, along with a significant decrease in the concentration of oxidative enzymes.. The results of the current study are in agreement with the results of the researcher's study (13) which indicated the high concentration of enzymes (ALT, AST) in the blood plasma of the group dosed with sodium benzoate, which had a detrimental effect on all parts of the body, including the liver, being the first center for the treatment of toxins in the body. The release of these enzymes into the bloodstream as a result of destroying the walls of the liver cells, thus increasing their concentration in the serum.…”
Section: Discussionsupporting
confidence: 89%
“…Firstly: The results of the current study showed a clear increase in the concentration of liver enzymes in the blood serum of animals treated with sodium benzoate at a concentration of (250) mg / kg of body weight, along with a significant decrease in the concentration of oxidative enzymes.. The results of the current study are in agreement with the results of the researcher's study (13) which indicated the high concentration of enzymes (ALT, AST) in the blood plasma of the group dosed with sodium benzoate, which had a detrimental effect on all parts of the body, including the liver, being the first center for the treatment of toxins in the body. The release of these enzymes into the bloodstream as a result of destroying the walls of the liver cells, thus increasing their concentration in the serum.…”
Section: Discussionsupporting
confidence: 89%
“…Correspondingly, Chiaretti et al also showed that no significant association was found between CSF BDNF levels and neurologic outcome in 27 children, either 2 or 48 hours after moderate and severe TBI (Chiaretti et al, 2003). Similarly, this study observed no correlation between baseline plasma BDNF levels and short-term fatal outcome (Damayanti et al, 2021).…”
Section: Comparative Analysis Of Bdnf Expression Results At 24 and 48...supporting
confidence: 62%
“…4). and subjected to microscopical examination at 10x magnification , and scored into 1-5 scales (1+=no perceptible motion, 2+=few spermatozoa move without forming any waves, 3+=small slow moving waves, 4+=vigorous movement with moderately rapid wave and eddies and 5+=dense,rapidly moving waves and eddies) (6).…”
Section: Semen Evaluation Sperm Motility Mass Activitymentioning
confidence: 99%